Designing Competency-Based Curriculum in Higher Education: An Evidence-Informed Framework for Outcomes, Assessment, and Program Coherence - Nguyen Thi Lan Anh Nguyen Thi Lan Anh (Kalam Practica Media, 2025)
Competency-based education (CBE) has gained considerable momentum across higher education systems worldwide as institutions face intensifying expectations to demonstrate that graduates possess not only disciplinary knowledge but the transferable, integrative capabilities that professional practice, civic life, and lifelong learning genuinely demand. Yet adoption frequently stalls or produces superficial results when competency statements remain abstract, when assessments fail to generate credible evidence of actual mastery, or when faculty experience CBE as an administrative relabeling exercise that demands compliance without offering pedagogical substance. This evidence-informed conceptual paper synthesizes scholarship on constructive alignment, curriculum coherence, program-level assessment design, and assessment validity principles to propose a practical, integrated framework for competency-based curriculum innovation in higher education. Drawing on research traditions in learning outcomes design, authentic assessment, formative feedback, and educational governance, the paper articulates four interdependent domains: (a) competency architecture and progression design that specifies observable performance at multiple proficiency levels; (b) assessment blueprinting and moderation routines that produce trustworthy evidence of mastery across diverse task contexts; (c) mastery-oriented learning design and feedback cycles that create the revision opportunities through which competence genuinely develops; and (d) governance and quality assurance structures that protect equity, credential portability, and public trust. Three conceptual tables operationalize the framework: a competency architecture template, an assessment blueprint connecting competencies to evidence artifacts and moderation routines, and a program coherence checklist for academic leaders and curriculum design teams. The paper concludes with implications for academic leaders, curriculum designers, and quality assurance agencies seeking to implement CBE as a substantive pedagogical and assessment reform rather than an administrative relabeling of existing practices.